Widespread bodily pain is not associated with the presence of painful TMJ osteoarthritis: a case control study - Panol Hanzara; Vivaldi Daniela; Di Giosia Massimiliano; Lim Pei Feng (EDP Sciences, 2021)
Purpose: Temporomandibular Joint Arthralgia (TMJA) in the absence of osteoarthritis has not been thoroughly studied. We aimed to investigate the presence of comorbid bodily pain conditions (CBPC) in patients with TMJA with and without TMJOA and hypothesized that TMJOA is not associated with a higher presence of CBPC. Methods: This is a retrospective study involving patients at the University of North Carolina Orofacial Pain Clinic between 2010 and 2014 with TMJA according to the RDC/TMD criteria [1]. Cases fulfilled the Ahmad classification for TMJOA [2], and had TMJA (TMJA+OA), while controls had TMJA only (TMJA-OA). Data was collected from reports of Cone-Beam Computerized Tomography (CBCT). CBPC were self-reported. Results: Twenty-eight cases (TMJA+OA) and 25 controls (TMJA-OA) were included. The mean age of cases and controls (P = 0.027) and mean pain duration differed (P = 0.031). However, the gender distribution (P = 0.552), mean pain intensity (P = 0.381), mean number of painful muscles upon palpation (P = 0.759) and mean number of CBPC (P = 0.575) were not different. At least one CBPC was reported by 68% cases and 72% control subjects (P = 0.743). Conclusions: In this group of patients with TMJA, the presence of CBPC was high and not associated with the presence of TMJOA. This finding suggests that CBPC and TMJOA occur independently.